Development of E-learning to Improving Knowledge Fishing Capability for Fishermen in East Nusa Tenggara, Indonesia - Yatimah, Durotul; Wasan, Aan; Kustandi, Cecep (Universitas Negeri Semarang, 2022)
E-learning is one of the factors that can affect the quality and quality of training, in this case, village assistants for fishing communities. E-learning provides non-formal distance interactions to carry out learning activities by carrying out activities including obtaining learning materials, learning resources, guides or step-by-step guidance or tutorials. The purpose of this study is to present a Village Assistant information system framework for fishermen in East Nusa Tenggara Province, because there is a growing concern that fishermen need empowerment using e-module technology. Our study uses a module development research methodology with quantitative and qualitative approaches. The results of data analysis show that the village companion e-module has the potential to empower fishermen. empowerment e-module suggesting access to information, competence, impact; self-determination, and meaning are components of empowerment for fishermen in NTT. Improved communication, opportunities to access fishing regulations, access to health and safety information, increased confidence related to the capabilities, and opportunities for professional development of fishermen. Potential empowerment results from the use of e-learning for village assistants. Comprehensive e-learning development for fishermen empowerment, because most of the literature approaches the economic point of view of fishermen, not in an organizational setting. This study contributes by providing practical knowledge to fishermen, government, and development organizations in the empowerment process, components, and results of empowerment using e-learning